2011
DOI: 10.1590/s0044-59672011000100016
|View full text |Cite
|
Sign up to set email alerts
|

Regeneración natural de nueve especies maderables en un bosque intervenido de la Amazonia Boliviana

Abstract: RESUMENUn aspecto fundamental del manejo forestal sostenible, es el mantenimiento de la regeneración natural en los bosques aprovechados. A corto y largo plazo, el aprovechamiento forestal tiene varias consecuencias, sobre la regeneración natural de las especies forestales. Esta investigación, compara la abundancia de la regeneración natural y la distribución espacial de plántulas de nueve especies maderables, entre un bosque aprovechado y un testigo. La abundancia y estructura espacial, fue determinada median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…As no large reduction in seedling and sapling densities was observed (Fig. ), it can be concluded that RIL does not seem to negatively impact the regeneration of the species studied, in common with findings elsewhere (Swaine & Agyeman , Gómez , Edwards et al . ).…”
Section: Discussionsupporting
confidence: 89%
“…As no large reduction in seedling and sapling densities was observed (Fig. ), it can be concluded that RIL does not seem to negatively impact the regeneration of the species studied, in common with findings elsewhere (Swaine & Agyeman , Gómez , Edwards et al . ).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the other two PST species, D. odorata and H. courbaril had low regeneration density in the studied area, as in other Amazonian locations (Gómez, 2011). Despite an increase in recruitment rate of D. odorata in the first year after harvesting, RIL did not affect its density.…”
Section: Densitymentioning
confidence: 52%
“…In tropical forests, regeneration may depend on natural disturbances (Fredericksen and Putz, 2003). Disturbances caused by logging may affect regeneration of valuable tree species in different ways (Gómez, 2011;Herrero-Jáuregui et al, 2011). Canopy opening increases the density and growth rates of both light-demanding (Nabe-Nielsen et al, 2007) as well as shade-tolerant species (Toledo-Aceves et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used this quantification of the entire world's rainforests (Jardim & Hosokawa, 1986;Holmgren;Persson, 2002;Grogan et al, 2008;Assis & Wittmann, 2011;Gómez, 2011;Mendes et al, 2013). In this sense, the size limit of the NR is very arbitrary and depends on the objectives of the evaluation.…”
Section: Regeneração Natural Em Florestas Tropicaismentioning
confidence: 99%